2000
DOI: 10.1093/jat/24.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Aluminum Phosphide Poisoning

Abstract: A 39-year-old man committed suicide by ingestion of aluminum phosphide, a potent mole pesticide, which was available at the victim's workplace. The judicial authority ordered an autopsy, which ruled out any other cause of death. The victim was discovered 10 days after the ingestion of the pesticide. When aluminum phosphide comes into contact with humidity, it releases large quantities of hydrogen phosphine (PH3), a very toxic gas. Macroscopic examination during the autopsy revealed a very important asphyxia sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 6 publications
2
44
1
1
Order By: Relevance
“…ASN-acetylcysteine use which have cellular regenerative properties and antioxidant effects, and usage of glutathione and magnesium are some of recommended treatment methods 2 . Anger et al reported that firstly symptomatic treatment, neutralization with gastric lavage and potassium permanganate application and intravenous application of magnesium sulfate for antioxidant effects is suggested in early treatment period 17 . Additionally, it was reported that using atropine, pralidoxime and magnesium would decrease morbidity and mortality in aluminum phosphide intoxication 15 .…”
Section: Discussionmentioning
confidence: 99%
“…ASN-acetylcysteine use which have cellular regenerative properties and antioxidant effects, and usage of glutathione and magnesium are some of recommended treatment methods 2 . Anger et al reported that firstly symptomatic treatment, neutralization with gastric lavage and potassium permanganate application and intravenous application of magnesium sulfate for antioxidant effects is suggested in early treatment period 17 . Additionally, it was reported that using atropine, pralidoxime and magnesium would decrease morbidity and mortality in aluminum phosphide intoxication 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal liver function tests in non-fatal cases of poisoning also suggest the presence of a type of pathology in the liver (19)(20)(21)(22)(23). Nevertheless, the morphologic findings in the liver in cases of phosphine poisoning have only been examined in very limited studies with small sample sizes (22,24,25 in Iran on liver biopsies from 37 patients who had died from zinc phosphide intoxication found that in all cases there were injury symptoms, which ranged from congestion to necrosis in the liver at different stages (26). Thirteen of our patients had high levels of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reports to the National Poisons Centre in Delhi indicate that aluminium phosphide is the pesticide most commonly ingested by children (Gupta, et al, 2003). Much smaller numbers or only sporadic cases of phosphide poisoning have been reported from the remainder of the world, including Australia (Nocera, et al, 2000), Denmark (Andersen, et al, 1996), France (Anger, et al, 2000), Germany ), Greece (Frangides & Pneumatikos, 2002), Iran (Pajoumand, et al, 2002), Jordan (Abder-Rahman, et al, 2000, Morocco (Idali, et al, 2005;Hajouji, et al, 2006;, Nepal (Lohani, et al, 2000), Sri Lanka (Roberts, et al, 2006), Turkey , the United Kingdom Lawler & Thomas, 2007), Canada, the United States (Broderick & Birnbaum, 2002, the former USSR (Rimalis & Bochkarnikov, 1978), and Yugoslavia (Curcic & Dadasovic, 2001). A single death from ingestion of a falsely labeled rodenticide bait has been reported (Azoury & Levin, 1998).…”
Section: Ingestion Of Phosphidesmentioning
confidence: 97%